BRAND TRUST DALAM PERSPEKTIF KONSUMEN: SEBUAH SYSTEMATIC LITERATURE REVIEW TERHADAP FAKTOR DAN IMPLIKASINYA - Ramayani Yusuf; Istiharini Istiharini; Heny Hendrayati (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Brand trust is a critical element in building long-term relationships between brands and consumers. In the context of increasingly intense market competition, understanding the factors that influence brand trust and its implications for consumer behavior is essential for both business practitioners and academics. This study aims to identify the factors influencing brand trust from the consumer perspective and its implications for brand loyalty, consumer satisfaction, and repurchase intention.This research employs a Systematic Literature Review (SLR) method, analyzing 15 scholarly articles published in indexed journals between 2000 and 2023. The articles were selected based on their relevance to the topics of brand trust, its forming factors, and its implications. Data were analyzed qualitatively to identify key patterns and findings. The literature synthesis reveals that brand trust is influenced by several key factors, including: (1) product quality, (2) brand reputation, (3) consumer experience, (4) transparent brand communication, and (5) brand consistency in fulfilling promises. Additionally, brand trust has significant implications for enhancing brand loyalty, consumer satisfaction, and repurchase intention. This study also finds that brand trust acts as a mediator between service quality and consumer loyalty. Brand trust is a multidimensional construct built through the interaction of various factors, both from the brand and consumer experience perspectives. The practical implication of these findings is the importance for companies to focus on consistency, transparency, and quality in building consumer trust. This study contributes theoretically by mapping the factors that shape brand trust and its implications, while also offering recommendations for future research to explore different industrial and cultural contexts.